Spent coffee grounds: A potential commercial source of phytosterols. (30th September 2020) - Nzekoue, Franks kamgang; Khamitova, Gulzhan; Angeloni, Simone; Sempere, Alba Nácher; Tao, Jing; Maggi, Filippo; Xiao, Jianbo; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni
Highlights: Analysis of phytosterols (PS) in spent ground coffee (SGC) by HPLC. Acidic sonication followed by saponification increase the extraction yield of PS. The most abundant PS in SGC are β-sitosterol, campesterol and stigmasterol. SGC is a high source of PS (343.4–1146.3 mg kg −1 ). SGC can be used as a sustainable alternative to corn and tall oil in PS industry. Abstract: This study sought to determine the content of phytosterols (PS) in spent coffee grounds (SCG) to assess a novel industrial application of this coffee by-product as a commercial source of PS. Four PS were extracted and analyzed from 14 SCG samples from 12 countries. Sonication in acidic conditions followed by saponification resulted determinant for PS extraction. PS were identified by high-performance liquid chromatography-diode array detector (HPLC-DAD) after derivatization. In the order of abundance, the PS were β-sitosterol (188.5–688.5 mg kg −1 ), campesterol (48.6–214.5 mg kg −1 ), stigmasterol (58.9–188.5 mg kg −1 ), and cycloartenol (14.6–65.8 mg kg −1 mg kg 1 ). Total PS fraction ranged from 343.4 mg kg −1 to 1146.3 mg kg −1 of SCG with an average level of 618.2 ± 195.4 mg kg −1 . Considering the millions of tons of SCG produced every year, this by-product could be a sustainable source of PS to fill a growing global demand.